KONTRIBUSI GURU PENDIDIKAN AGAMA ISLAM TERHADAP PENANAMAN SIKAP RELIGIUS SISWA DI SMK NU KEJAJAR WONOSOBO - Salamun, Ilham; Zuhdi, Ahmad; Fatiatun, Fatiatun (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2024)
This study aims to, 1. To find out the religious attitude of students at SMK NU Kejajar Wonosobo, 2. To find out the contribution of Islamic religious education teachers at SMK NU Kejajar Wonosobo, 3. To find out the supporting and inhibiting factors of Islamic Religious Education teachers towards inculcating religious attitudes students at SMK NU Kejajar Wonosobo. Using a qualitative descriptive method, the subjects of this study were: Principals of Kejajar NU Vocational Schools, Head of Curriculum for Kejajar NU Vocational Schools, Islamic Religious Education Teachers of Kejajar NU Vocational Schools, and Students of Kejajar NU Vocational Schools Wonosobo.This research is a field research using a qualitative approach, namely an approach that aims to describe and understand the visible meaning, namely the Contribution of Islamic Religious Education Teachers to inculcating students' religious attitudes at SMK NU Kejajar Wonosobo. The research subjects were: Principals of Kejajar NU Vocational Schools, Head of Curriculum for Kejajar NU Vocational Schools, Islamic Religious Education Teachers and Students of Kejajar NU Vocational Schools Wonosobo. Methods of data collection using interviews, observation, and documentation. Data analysis used descriptive qualitative analysis.The results of the study show that the religious attitude of students at SMK NU Kejajar is still lacking because this is in accordance with the results of interviews that have been conducted by the author. The contribution of Islamic Religious Education teachers to inculcating students' religious attitudes at SMK NU Kejajar is very large because Islamic Religious Education teachers at SMK NU Kejajar are required to be facilitators, motivators and inspirers of students to instill religious attitudes and learn Islam well. Supporting factors such as students' own awareness of the importance of being disciplined and caring for fellow students. Because the process of instilling Islamic religious values in this school is from the entire role of the teacher council in guiding and always providing encouragement to be able to make students have good morals in their daily life. The inhibiting factors can be the lack of awareness of the student himself, the lack of support from his family, and also the most influential, usually from his friends, sometimes there are friends who are naughty, lack discipline and so on. Because the group of friends sometimes also outside school so that, causing them to be free they can no longer be controlled, their background is from a broken home family and the association is not good among friends. Keywords: Contribution, Planting, Religious